Analisis Penghimpunan Dan Pendistribusian Zakat Di Baitulmal Kota Subulussalam Saat Pandemi Covid-19 - Fadila Capah, Nurhalizah; Arif, Muhammad (Proceedings of International Conference on Islamic Economic Finance and Social Finance (ISSN: XXXX-XXXX) (ESSN: XXXX-XXXX), 2022)
Since January 2020, the world has been rocked by the COVID-19 outbreak. All countries, including Indonesia, have felt the impact. The impact of COVID-19 is multidimensional, one of which is the zakat institution such as Baitulmal. With this outbreak, the income of Muzaki has decreased, thus affecting the collection of zakat. However, this did not happen at Baitulmal in Subulussalam City, the increase in zakat and infaq collection has increased every year, and the highest increase occurred in 2020, when the COVID-19 pandemic broke out, amounting to IDR 1,525,319,891 when compared to zakat collection in 2019 of IDR 1,084,081,052, the collection of zakat and infaq at Baitulmal in Subulussalam City increased by 441,238,839 from the previous year. In addition to the zakat collection carried out, Baitulmal Kota Subulussalam is responsible for allocating zakat and infaq to eight asnaf, among the zakat distribution programs are the poor, the elderly, the disabled, the gharimin, converts, educational assistance, home renovation, business capital, Amil and other Islamic activities. During the pandemic, Baitulmal Kota Subulussalam also utilized zakat and infaq by distributing basic necessities to the community. activities carried out both in the office and in the field, all employees comply with the Health Protocol as per the regulations that have been set.